From Gregory the Great to Sergius I: A Contribution to the Study of the Ktetorship Activity of the Popes in Rome and the Cults of the Early Christian Martyrs - Tutić, Ognjen Lj. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper is dedicated to the scholarly examination of the papal ktetorship endeavors in Rome, spanning from the late 6th century to the early 8th century, in the context of the systematic development of the cults of early Christian martyrs who, through their suffering, sanctified the eternal city. Research has shown that it was the cults of early Christian martyrs that were used as the fundamental strongholds of the personal, almost ruling authority of the popes, which shaped the identity of the city as the universal center of the entire Christian ecumene. Throughout the early Middle Ages, the popes, as the main ktetors and bearers of artistic production, created the city’s identity by expanding the network of temples which, in a significant number of cases, were dedicated to the members of the early Christian congregation—the princes of the apostles Peter and Paul, but also other martyrs whose relics, systematically or magically, were discovered inter or extra muros. The discoveries of graves, remains or other relics of early Christian martyrs represented significant incentives for papal ktetorship activity, renovations of already existing and construction of new churches, and the formation and consecration of altars and oratories, all for the purpose of highlighting Rome, the papal city, as the nucleus of the Christian universe. In the paper, special attention is devoted to a deeper consideration of the documented temples, chapels and oratories dedicated to the martyrs in Rome, which were restored or newly built thanks to the merits of the popes. Considering the socio-political and cultural-historical circumstances of the pontificate of the popes who reigned during the specified period, along with the predominant concepts that influenced early medieval collective and private piety towards martyrs, this work is dedicated to showcasing the most outstanding examples of art and visual culture in the eternal city. Furthermore, the phenomenon of assimilating martyrs, whose veneration did not adhere to ad sanctos, but instead represented instances of importing martyr cults from various regions of the Christian world, is a specific focus of our examination. Accordingly, the paper presents conclusions regarding the systematic expansion of the network of temples dedicated to martyrs in the sacred topography of Rome, the essence of which, above all, was papal propaganda aimed at emphasizing the axiomatic primacy of the city, but also the institution of the papacy within the boundaries of the Christian universe.